ACTUALIZATION OF GOLDEN AURY'S GOVERNANCE POLICY IN THE CONDITIONS OF ECONOMIC AND POLITICAL TRANSFORMATIONS OF THE WORLD FINANCIAL SYSTEM - Anna Pleshivtseva (Вестник Северо-Кавказского федерального университета, 2022)
Today, an increasing number of experts and analysts are inclined to the scenario of transformation of the global economy, in which the US currency will cease to play the role of the leading reserve unit of the planet. In the light of the regularly occurring financial crises, which each time have more severe consequences for the economies of individual countries and even regions, the question of building a new inancial world order, as well as payment instruments and funds supporting it, is being updated. In this regard, the future financial architecture assumes a revision of the role of gold, which to this day continues to be a powerful inancial guide for states in the course of their economic and political activities.